Salivary Exosomes: From Waste to Promising Periodontitis Treatment - Nik Mohamed Kamal, Nik Nur Syazana; Shahidan, Wan Nazatul Shima (Frontiers in Physiology, 2022)
Periodontitis is a chronic inflammatory condition that causes tooth loss by destroying the supporting components of the teeth. In most cases, it is difficult to diagnose early and results in severe phases of the disease. Given their endogenous origins, exosomes, which are rich in peptides, lipids, and nucleic acids, have emerged as a cell-free therapeutic approach with low immunogenicity and increased safety. Because the constituents of exosomes can be reprogrammed depending on disease states, exosomes are increasingly being evaluated to act as potential diagnostic biomarkers for dental disease, including periodontitis. Exosomes also have been demonstrated to be involved in inflammatory signal transmission and periodontitis progression in vitro, indicating that they could be used as therapeutic targets for periodontal regeneration. Nevertheless, a review on the involvement of salivary exosomes in periodontitis in impacting the successful diagnosis and treatment of periodontitis is still lacking in the literature. Thus, this review is intended to scrutinize recent advancements of salivary exosomes in periodontitis treatment. We summarise recent research reports on the emerging roles and characteristics of salivary exosomes, emphasizing the different expressions and changed biological roles of exosomes in periodontitis.